Integrated riverside development as urban public spaces: a case study of Bangkinang riverside - Wahyu Hidayat; Muhd. Arief Al Husaini (Institute of Computer Science (IOCS), 2022)
Bangkinang is the capital of Kampar regency, Riau Province. Currently, the city of Bangkinang does not have public space so people do not have a comfortable space for various outdoor activities. The riverside area of Bangkinang city in Bangkinang City village has the potential to be used as a water-based public space. The purpose of this research is to find a formulation of public space development that can improve the quality of the environment and comfortable outdoor space. This research method is a descriptive qualitative method. The initial stage of research is by collecting data through observation and interviews. Furthermore, analysis and conceptualization are carried out. The results of the analysis and conceptual will be used as the basis for decision-making on regional development such as determining zoning, function, and placing facilities. The result of this study is the design of the arrangement of the Bangkinang Riverside area. The concept of this arrangement is Tungku Tigo Sajarangan, Tali Bapilin Tigo.